Political Corruption and How to Combat - Aris Sarjito (Journal of Governance, 2023)
Abstract:Political corruption refers to the misuse of public office for personal gain or the abuse of political power for illegitimate ends. It manifests itself in various forms, including bribery, cronyism, nepotism, embezzlement, fraud, and abuse of public resources. Political corruption not only undermines the rule of law and democracy but also weakens public trust in government institutions and hinders economic development.The detrimental effects of political corruption are far-reaching and can have a significant impact on society as a whole. It increases inequality and poverty, reduces public access to essential services, and deprives citizens of their fundamental rights and freedoms. Moreover, political corruption also distorts public policies, compromises public safety, and promotes political instability.Overcoming political corruption requires the implementation of effective anti-corruption laws and institutions that hold public officials accountable for their actions. Such efforts require a combination of political will, public participation, and international cooperation. However, addressing political corruption is an ongoing challenge, and continuous efforts are required to prevent its resurgence in different forms and contexts.Keywords: Corruption, Government officials, Political corruption.